Soft phonon modes from off-center Ge atoms lead to ultralow thermal conductivity and superior thermoelectric performance in n-type PbSe–GeSe - Luo, Zhong-Zhen (2020)
Historically PbSe has underperformed PbTe in thermoelectric efficiency and has been regarded as an inferior relative to its telluride congener. However, the fifty-fold greater natural abundance of Se relative to Te makes PbSe appealing as a thermoelectric material. We report that the n-type GeSe-alloyed PbSe system achieves a peak figure of merit, ZT, of ∼1.54 at 773 K and maintains ZT values above 1.2 over a broad temperature range from 623 K to 923 K. The highest performing composition is Sb-doped PbSe–12%GeSe, which exhibits an ultralow lattice thermal conductivity of ∼0.36 W m−1 K−1 at 573 K, close to the limit of amorphous PbSe. Theoretical studies reveal that the alloyed Ge2+ atoms prefer to stay at off-center lattice positions, inducing low frequency modes. The Ge atoms also cause the unexpected behavior where the next nearest atom neighbors (6 Pb atoms) oscillate at lower frequencies than in pure PbSe leading to a large reduction of the Debye temperature and acoustic phonon velocity. The Pb0.9955Sb0.0045Se–12%GeSe system also shows Ge-rich precipitates and many aligned dislocations within its microstructure which also contribute to phonon scattering. The resultant average ZT (ZTavg), a broad measure of the material's potential for functional thermoelectric modules, is 1.06 from 400 K to 800 K, the highest among all previously reported n- and p-type PbSe. This value matches or exceeds even those of the best n-type PbTe-based thermoelectric materials.